The Effect Of Return on Equity, Net Profit Margin, and Cash Ratio on Tobin's Q at PT. Steel Pipe Industry of Indonesia, Tbk in 2014-2021 - Desi Berliantiana Pudji Lestari; Reswanda (Journal of World Conference (JWC), 2022)
This research aims to see the effect of Return On Equity, Net Profit Margin, and Cash Ratio on Tobin's Q. This research was conducted in one company, PT. Steel Pipe Industry Of Indonesia, Tbk in 2014-2021. The independent variables in this research use the ratio of Return On Equity, Net Profit Margin, and Cash Ratio. And the dependent variable in this study is Tobin's Q. The results of this research indicate that the Return On Equity variable has a positive and significant influence on Tobin's Q, Net Profit Margin has a positive and significant effect on Tobin's Q. While the Cash Ratio variable has a negative influence on Tobin's Q.